Tourists’ Hotel Booking Preferences Changed by the COVID-19 Outbreak - RODYU, Sauwanee; CHEABLAM, Onanong; NANTAVISIT, Nuttaprachya; LING, Yang (Journal of Environmental Management and Tourism; Vol 14 No 2 (2023): JEMT, Volume XIV, Issue 2(66), Spring 2023, 2023)
This study aims to identify the characteristics and behaviors of Thai tourists during the pandemic, to investigate the marketing factors in tourism affecting their hotel reservations during the pandemic, and to analyze which marketing factors in tourism have affected their decisions on hotel reservations during the pandemic. Online questionnaires were used to collect data from 385 people. The data was analyzed by descriptive statistics and a confirmatory factor analysis (CFA), while the hypotheses were tested by inferential statistics. The results indicated that Thai tourists considered significant factors in tourism marketing. It included hotel products, room rates, reservation channels, promotions, personnel, features, and services. Furthermore, the hypothesis test indicated that Thai tourists had different hotel reservation behaviors during the pandemic. Gender, age, region, occupation, monthly income, travel goal, accommodation type, length of stay, travel companion, and reservation channel played a statistically significant role at 0.05. Therefore, this study will support hoteliers in planning their strategy to handle situations during the pandemic and prepare for another health crisis in the future. Furthermore, it will benefit the hotel industry by showing ways to develop and improve their products and services to meet tourist demand during a pandemic.